Job Satisfaction and Teachers’ Performance in Secondary Schools in Gulu District - Lamaro, Gloria; Okello, Proscovia Daphine (East African Journal of Education Studies, 2023)
Education outcomes depend on the quality and effectiveness of their workers. Teachers who are satisfied with their jobs perform their duties effectively and efficiently. This study aimed to investigate the relationship between job satisfaction and teachers’ performance in secondary schools in Gulu district. A total of 174 secondary school teachers in Gulu district were selected as respondents of the study and a descriptive correlation design was used in order to see the relationship of the variables in eight sample secondary schools in the district. Data was analysed using person’s correlation with the help of SPSS software to obtain the values. The findings indicate that there is high correlation between job satisfaction and teachers’ performance, which show that high job satisfaction contributes to high teachers’ performance. The study concludes that there is a significant relationship between job satisfaction and teachers’ performance. Based on the findings and conclusions the research recommends that; the government should strengthen and harmonise teachers’ pay in order for them to gain higher satisfaction on the job. Secondly, teachers be housed within the school to boost their job satisfaction and lastly, the teachers be treated equally without bias. Thirdly, the Ministry of Education and Sports should make policies, programs and projects for secondary school teachers to enhance job satisfaction and performance towards quality education